Studi Molekuler Rice tungro bacilliform virus pada Ratun Padi di Sidrap, Sulawesi Selatan melalui Pendekatan PCR - Sidik, Effi Alfiani; Ibrahim, E.; Firmansyah, F.; Khaerana, K. (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Sidik, E.A., Ibrahim, E., Firmansyah, F. & Khaerana, K. (2024). Molecular study of rice tungro bacilliform virus on rice ratoons in Sidrap, South Sulawesi through a PCR Approach. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 836–842). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Rice rungro bacilliform virus (RTBV) is a primary causes of tungro disease, which proses a significant threat to rice production in South Sulawesi. This study was conducted to identify the infection symptoms and presence of RTBV in rice retoon in Sidrap, South Sulawesi. Samples were collected using purposive sampling in area suspected of tungro virus infection, and symptom identification was performed. RTBV detection was carried out using Polymerase Chain Reaction (PCR). Symptoms observed included yellow to orange discoloration of leaves, leaf shortening, and narrowing of leaf blades. PCR results confirmed that the ratoon rice was infected by RTBV. These finding indicated ratoons may serve as a potential inoculum source for virus spread in the mext planting season, thus prolonging the infection cycle. Early detection of RTBV infection in the ratooning phase through molecular approaches is crucial to minimizing the risk of tungro disease spread.